Reply to: “Notes on Hofshi and Korsh 1972” - Hofshi, Rami; Korsh, James (Management Science, 1976)
Reply to: “Notes on Hofshi and Korsh 1972” (Joglekar, Prafulla. Notes on Hofshi and Korsh 1972. Management Sci. 22 (6) 717–720).